Enhanced foaming ability of thermoplastic polyurethane by crystallization during mold-opening foam injection molding with supercritical N2 as blowing agents - Sai Wang; Haoyang Feng; Jianming Hong; Guilong Wang (Journal of Materials Research and Technology, 2023)
This study provides an insight into the foaming of thermoplastic polyurethane (TPU), which was improved by the crystallization of hard segment domains. This study investigated the effects of packing time in the mold-opening foam injection molding (MOFIM) technology on the crystallization behavior of hard segments in TPU and the cell morphology of TPU foams. It was observed that the prolongation of the packing time, corresponding to a longer crystallization time before foaming, induced an increased crystallinity in the injection-molded TPU solids and foams due to the crystals becoming more close-packed. The enhancement of the foamability of TPU was attributed not only to the increased crystallinity of hard segments, but also to the broader distribution of crystals at the same crystallinity. Furthermore, TPU foams with greater hardness have smaller cell size, higher cell density, and narrower distribution in cell size owing to their higher viscosity and storage modulus than those with lower hardness prepared under the same conditions.